Ultrafast chemical lithiation of single crystalline silicon nanowires: in situ characterization and first principles modeling1. Issue 23 (13th March 2015) - Seo, Jong-Hyun; Chou, Chia-Yun; Tsai, Yu-Hao; Cho, Yigil; Seong, Tae-Yeon; Lee, Woo-Jung; Cho, Mann-Ho; Ahn, Jae-Pyoung; Hwang, Gyeong S.; Choi, In-Suk
<x xml:space="preserve">Abstract</x> Through a combined density functional theory and in situ scanning electron microscopy study, we demonstrate the ultrafast chemical lithiation of a single c-Si nanowire brought into direct contact with Li metal in the absence of an electric field.